2018
DOI: 10.1002/alr.22147
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes following culture‐directed vs non–culture‐directed antibiotics in treatment of acute exacerbations of chronic rhinosinusitis

Abstract: Culture-directed therapy improves long-term endoscopy scores but does not yield an advantage in improving short-term endoscopy scores, nor in improving short-term and long-term quality of life scores in CRS patients. A prospective study is necessary to examine the relevance of routine microbiologic cultures in CRS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
2
11
1
1
Order By: Relevance
“…Culture‐directed therapy for AECRS showed an improvement in Lund‐Kennedy endoscopy scores long term, but not in the short term. Furthermore, culture directed antibiotics does not improve short or long‐term QoL in CRS 1761 . This is in contrast to an earlier study that showed a decreased short‐term QoL improvement in the post ESS patients treated with culture inappropriate antibiotics, which is defined as at least 1 cultured organism resistant to or not covered by the prescribed post‐operative antibiotics.…”
Section: Acute Exaccerbation Of Chronic Rhinosinusitis (Aecrs)contrasting
confidence: 88%
“…Culture‐directed therapy for AECRS showed an improvement in Lund‐Kennedy endoscopy scores long term, but not in the short term. Furthermore, culture directed antibiotics does not improve short or long‐term QoL in CRS 1761 . This is in contrast to an earlier study that showed a decreased short‐term QoL improvement in the post ESS patients treated with culture inappropriate antibiotics, which is defined as at least 1 cultured organism resistant to or not covered by the prescribed post‐operative antibiotics.…”
Section: Acute Exaccerbation Of Chronic Rhinosinusitis (Aecrs)contrasting
confidence: 88%
“…Other authors who investigated populations similar to our study group (mainly post-ESS patients with correctly diagnosed AECRS) reported comparable findings [34][35][36][37][38]. The most commonly isolated pathogens were always S. aureus (25%-70%) and P. aeruginosa (9%-24%), while the "acute pathogens" S. pneumoniae, H. influenzae, and M. catarrhalis constituted only 10%-22% of all isolates.…”
Section: Microbiology and Antibiotic Resistance In Aecrssupporting
confidence: 84%
“…Other authors who investigated populations similar to our study group (mainly post-ESS patients with correctly diagnosed AECRS) reported comparable findings [34][35][36][37][38]. The most As explained above, due to uneven distribution of the bacteria among patients, the prevalence of phage-sensitive bacteria in the study group needs to be presented separately from the analysis of phage sensitivity in the bacterial isolates.…”
Section: Microbiology and Antibiotic Resistance In Aecrssupporting
confidence: 64%
“…In the study by Yan et al ., 21 empiric and culture-directed antibiotic therapy for acute exacerbation of chronic rhinosinusitis were analysed, and the authors pointed out that primary targeted treatment improved long-term endoscopy scores compared with empiric treatment. Nevertheless, in that study, the short- and long-term quality of life and short-term endoscopy scores were comparable.…”
Section: Discussionmentioning
confidence: 99%